PERAN ORANG TUA TERHADAP KESEHATAN ANAK DI KABUPATEN SINJAI - AB, Syamsuddin (Jurnal Berita Sosial, 2018)
The Role of Parents on Children’s Health In Sinjai District aims to describe the things parents do about the health of the child’s diet and other techniques. This research method uses a kind of qualitative approach that is done intensive, in-depth, detailed and comprehensive with the stages of doing exploration where the target of research by using phenomenology method, then formulate theories that lead researchers to seek more in the issues studied, while the technique data collection is natural setting with the sense that expected what kind of events experienced by individuals and not influenced by the presence of researchers in the family. Besides, the data were collected descriptive, in-depth interviews, observations (meticulous responses to pure sensory level), and documentation studies and data analysis techniques with Miles and Huberman’s model of data reduction, data presentation, and conclusions. The results of this study indicate that the role of parents who tekait health done since the child was born so that parents avoid the disease parents parents "bingkasadan and children not asittang, Breastfeeding related ASI first child after birth, children’s treatment of varying feeding schedule, play time or playground of the child, even the health of the parent’s pregnancy. Keywords: Parents Extremely Role In Children’s Health